Implementation of Ward and Peppard Methodology on IS/IT Strategic Planning (Case Study: Salatiga City Government) - Steven Lim; Agustinus Wijaya (Journal of Software Engineering Ampera, 2022)
Rapid advances in technology have made many organizations compelled to plan and execute business strategies to improve organizational performance, so an organization must have an information system strategic plan to support the achievement of business strategies. The Salatiga City Government already has and implements an information system to support business processes but has not yet been integrated into all regional apparatus organizations (OPD). Collecting data in this study using interviews and observations as well as analysis to determine the business environment and the IS/IT environment of the Salatiga City Government. The method used in this study is Ward and Peppard with Value Chain analysis, SWOT, Mc Farlan's Strategic Grid. This research produces a portfolio of applications to provide an overview in the application of IS/IT to align business strategy and vision and mission.